2014
DOI: 10.1007/s00114-014-1188-9
|View full text |Cite
|
Sign up to set email alerts
|

The innate responses of bumble bees to flower patterns: separating the nectar guide from the nectary changes bee movements and search time

Abstract: Nectar guides can enhance pollinator efficiency and plant fitness by allowing pollinators to more rapidly find and remember the location of floral nectar. We tested if a radiating nectar guide around a nectary would enhance the ability of naïve bumble bee foragers to find nectar. Most experiments that test nectar guide efficacy, specifically radiating linear guides, have used guides positioned around the center of a radially symmetric flower, where nectaries are often found. However, the flower center may be i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 29 publications
2
18
0
Order By: Relevance
“…Our results are also consistent with Johnson and Dafni (1998), in which bombyliid flies (Usia bicolor) landing on model flowers with radiating lines walked directly towards the point where the lines converged. The reduced NDTs on artificial flowers comprised of radiating lines which lead to the nectary over 'disjunct' guides where radiating lines lead away from the nectary in Goodale et al (2014) is also reminiscent of our findings. This shortened NDT on radiating flowers in the preference tests suggest there may be time benefits from radiating floral patterns when foragers encounter multiple flower species.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Our results are also consistent with Johnson and Dafni (1998), in which bombyliid flies (Usia bicolor) landing on model flowers with radiating lines walked directly towards the point where the lines converged. The reduced NDTs on artificial flowers comprised of radiating lines which lead to the nectary over 'disjunct' guides where radiating lines lead away from the nectary in Goodale et al (2014) is also reminiscent of our findings. This shortened NDT on radiating flowers in the preference tests suggest there may be time benefits from radiating floral patterns when foragers encounter multiple flower species.…”
Section: Discussionsupporting
confidence: 79%
“…1b). This radiating aspect of nectar guides appears to be important in terms of flower orientation to species such as bombyliid flies and bumblebees (Johnson and Dafni 1998;Goodale et al 2014). Considering these points, it would be of interest to explore the differences between these pattern types.…”
Section: Introductionmentioning
confidence: 99%
“…Visual signals are critical for pollinating bees seeking appropriate flowers for food resources, namely nectar for energy and pollen for protein (Goodale et al 2014). Some bee species are polylectic and thus use signals from a wide range of plant families, while the more specialized oligolectic and monolectic bees detect cues from fewer plant families (Milet-Pinheiro et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Many aspects of color vision in bees have been thoroughly studied (Lunau 1990(Lunau , 1991Lunau and Maier 1995;Lunau et al 1996;Chittka 1997;Vorobyev and Osorio 1998;Chittka 1999;Gumbert 2000;Spaethe et al 2001;Dyer and Chittka 2004;Lunau et al 2006;Chittka and Spaethe 2007;Whitney et al 2009;Goodale et al 2014). These studies have highlighted the complexity of bee attraction to flowers of different colors and patterns.…”
Section: Introductionmentioning
confidence: 99%
“…When the position of the nectary conflicted with the 'directions' given by an offcentre guide, unsuccessful novice bumblebee foragers spent significantly more time searching for nectar than when the nectar guides surrounded the nectary (Goodale et al, 2014). Using a similar experimental strategy of dissociating two variables, pattern type (radial vs. concentric) and location of the pattern elements (central vs. peripheral), we showed that both concentric elements and radial elements caused bumblebees to enter an artificial flower, as long as the elements were centrally located: both 'X' and 'O' marked the spot.…”
Section: Pattern Locationmentioning
confidence: 99%